Environment-friendly bio-based nano reinforced waterproof material as well as preparation method and application thereof
By introducing modified nanosilica, nano zinc oxide and nanomontmorillonite into bio-based materials, combined with bio-based fillers, we form environmentally friendly bio-based nano-enhanced waterproof materials, and solve the insufficient waterproof performance of existing bio-based waterproof materials. The problems of low mechanical strength and poor durability have achieved excellent waterproofing and mechanical properties, and are suitable for construction, transportation, aerospace and other fields.
Patent Information
- Application Number
- CN202411117721.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-13
AI Technical Summary
The existing bio-based waterproofing materials have problems such as insufficient waterproofing performance, low mechanical strength and poor durability, which limits their widespread use in practical applications.
Using bio-based fillers (such as polychizol, gelatin and sodium carboxymethylcellulose) with modified nanosilicon dioxide, nano zinc oxide and nanomontmorillonite, the formation of environmentally friendly biological products is formed through ultrasonic treatment and cross-linking reaction. Base nano-enhanced waterproof material to improve the waterproof performance and mechanical strength of the material.
It significantly improves the waterproof performance and mechanical strength of the material, extends the service life, reduces dependence on petroleum resources, reduces environmental pollution, and is suitable for many occasions with high waterproofing requirements.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of waterproof materials, and in particular to an environmentally friendly bio-based nano-enhanced waterproof material and a preparation method and application thereof. Background Art
[0002] With the development of society, people's living standards are gradually improving, and people's requirements for building quality are getting higher and higher; waterproof materials are applied on the surface of buildings, and a thin film is formed after water volatilization and hydration. It can isolate the surface of the building from water, thereby playing an anti-seepage and waterproofing role. At the same time, the strength and flexibility of the coating itself are used to make up for the small gaps caused by the activity of the building's base layer to block the infiltration of water. It is one of the building waterproof materials that the country focuses on promoting. At present, most of the organic materials that play a key role in waterproof materials are extracted and processed from non-renewable resources such as petroleum. With the proposal of the country's dual carbon goals, the application of non-renewable resources such as petroleum will be further restricted, and the application areas and quantity of biomass materials are bound to develop rapidly and greatly.
[0003] Traditional waterproof materials mostly rely on petroleum-based products. Although these materials have good waterproof properties, their production and use impose a heavy burden on the environment. In addition, petroleum-based waterproof materials may release harmful substances during production and degradation, posing a threat to the ecological environment and human health. With the global emphasis on environmental protection and sustainable development, the development of environmentally friendly bio-based waterproof materials has become a research hotspot. However, existing bio-based waterproof materials often have problems such as insufficient waterproof performance, low mechanical strength, and poor durability, which limits their widespread use in practical applications. Summary of the invention
[0004] In view of this, the present invention proposes an environmentally friendly bio-based nano-enhanced waterproof material and a preparation method, application and system, aiming to solve the problems of insufficient waterproof performance, low mechanical strength and poor durability of existing bio-based waterproof materials in current technology.
[0005] On the one hand, the present invention proposes an environmentally friendly bio-based nano-enhanced waterproof material, in which the proportions of various raw materials are as follows: 80-100 parts of bio-based filler, 7-10 parts of modified nano-silicon dioxide, 7-10 parts of nano-zinc oxide, 5-7 parts of nano-montmorillonite, 3-5 parts of dispersant, 3-5 parts of softener, and 2-3 parts of cross-linking agent.
[0006] Furthermore, it also includes 1-2 parts of antioxidant and 1-2 parts of citric acid; wherein the antioxidant is one or a mixture of vitamin E, butylated hydroxyanisole, sodium bisulfite and glutathione.
[0007] Furthermore, the bio-based filler is one or a mixture of chitosan, gelatin and sodium carboxymethyl cellulose.
[0008] Furthermore, the dispersant is one or a mixture of polyvinyl pyrrolidone, polyethylene glycol and ammonium polyacrylate.
[0009] Furthermore, the softener is glycerol or triglyceride.
[0010] Furthermore, the cross-linking agent is one of a mixture of borax and a silane coupling agent in a ratio of 3 parts borax to 1 part silane coupling agent or a mixture of epoxy resin and a silane coupling agent in a ratio of 10 parts epoxy resin to 1 part silane coupling agent.
[0011] On the other hand, the present invention also proposes a method for preparing an environmentally friendly bio-based nano-enhanced waterproof material, comprising the following steps:
[0012] S1: dissolving chitosan in 1% volume fraction acetic acid solution, stirring to form a chitosan solution, dissolving gelatin and sodium carboxymethyl cellulose in deionized water, stirring until completely dissolved, to form a gelatin solution and a carboxymethyl cellulose solution;
[0013] S2: mixing nano silicon dioxide, nano zinc oxide and nano montmorillonite in a ratio of 7-10:7-10:5-7, adding deionized water, and dispersing the nano silicon dioxide, nano zinc oxide and nano montmorillonite by ultrasonic treatment;
[0014] S3: Mix the chitosan solution, gelatin solution and sodium carboxymethyl cellulose solution in a ratio of 2:2:3 and stir thoroughly; add the dispersed nanoparticles into the mixed solution and continue stirring until uniform;
[0015] S4: adding a cross-linking agent, controlling the reaction temperature and stirring until cross-linking is completed;
[0016] S5: evenly coating the cross-linked solution on a glass plate or a fabric substrate; drying the coated substrate to form a uniform waterproof film; peeling the dried waterproof film from the substrate to form an environmentally friendly bio-based nano-enhanced waterproof material.
[0017] Furthermore, the ultrasonic treatment time is more than thirty minutes.
[0018] Furthermore, in S4, the cross-linking temperature is 60° C. and the stirring time is more than two hours.
[0019] On the other hand, the present invention also proposes an environmentally friendly bio-based nano-enhanced waterproof material for use in the fields of construction, transportation, and aerospace.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention provides an environmentally friendly bio-based nano-enhanced waterproof material, the bio-based filler and nano-material used are environmentally friendly materials, which can reduce dependence on petroleum resources and reduce environmental pollution. By introducing modified nano-silicon dioxide, nano-zinc oxide and nano-montmorillonite, the waterproof performance of the material is significantly improved, making it suitable for a variety of occasions with high waterproof requirements. The cross-linking agent in the present invention can effectively improve the binding force between the bio-based filler and the nano-material, thereby enhancing the mechanical strength and durability of the material. The added antioxidant and citric acid can improve the antioxidant performance of the material and extend the service life of the material. The combination of the bio-based filler and the nano-material in the present invention not only provides excellent waterproof performance, but also gives the material good biocompatibility and antibacterial properties. The preparation method of the present invention is simple, easy to operate, suitable for large-scale production, and conducive to reducing production costs. The environmentally friendly bio-based nano-enhanced waterproof material of the present invention can be widely used in the fields of construction, transportation, aerospace, etc., and has broad market prospects. By adopting bio-based materials, pollution to the environment is reduced, which meets the requirements of green environmental protection. Moreover, the addition of nanoparticles significantly improves the mechanical properties, heat resistance and waterproofness of the material, so that the material performs excellently in various applications. Most of the bio-based materials used are biodegradable, avoiding the environmental problems caused by traditional petroleum-based polymers. Natural polymers such as chitosan and gelatin have good biocompatibility, which makes this material also potentially applicable in the medical field. Compared with some high-performance synthetic materials, bio-based materials are lower in cost, more widely available, and more economical. DETAILED DESCRIPTION
[0021] Traditional waterproof materials mostly rely on petroleum-based products. Although these materials have good waterproof properties, their production and use impose a heavy burden on the environment. In addition, petroleum-based waterproof materials may release harmful substances during production and degradation, posing a threat to the ecological environment and human health. With the global emphasis on environmental protection and sustainable development, the development of environmentally friendly bio-based waterproof materials has become a research hotspot. However, existing bio-based waterproof materials often have problems such as insufficient waterproof performance, low mechanical strength, and poor durability, which limits their widespread use in practical applications.
[0023] Therefore, an embodiment of the present invention provides an environmentally friendly bio-based nano-enhanced waterproof material, in which the proportions of various raw materials are: 80-100 parts of bio-based filler, 7-10 parts of modified nano-silicon dioxide, 7-10 parts of nano-zinc oxide, 5-7 parts of nano-montmorillonite, 3-5 parts of dispersant, 3-5 parts of softener, and 2-3 parts of cross-linking agent.
[0024] In this preferred embodiment, 1-2 parts of antioxidant and 1-2 parts of citric acid are also included; wherein the antioxidant is one or a mixture of vitamin E, butylated hydroxyanisole, sodium bisulfite and glutathione.
[0025] In this preferred embodiment, the bio-based filler is one or a mixture of chitosan, gelatin and sodium carboxymethyl cellulose.
[0026] In this preferred embodiment, the dispersant is one or a mixture of polyvinyl pyrrolidone, polyethylene glycol and ammonium polyacrylate.
[0027] In this preferred embodiment, the softener is glycerol or triglyceride.
[0028] In this preferred embodiment, the crosslinking agent is one of a mixture of borax and silane coupling agent in a ratio of 3 parts borax to 1 part silane coupling agent or a mixture of epoxy resin and silane coupling agent in a ratio of 10 parts epoxy resin to 1 part silane coupling agent.
[0029] It is understood that bio-based fillers are the main component of the material, providing strength and toughness. Preferred fillers include chitosan, gelatin and sodium carboxymethyl cellulose, which are all renewable natural materials with good environmental performance. Modified nano-silica is used as a nano-enhancer. Modified nano-silica can significantly improve the mechanical properties and waterproof properties of the material, making it more durable. Nano zinc oxide has antibacterial and UV protection functions, which can extend the life of the material and improve its durability. Nano-montmorillonite can enhance the barrier properties of the material and improve its waterproofness and water resistance. Dispersants can improve the dispersibility of nanomaterials so that they are evenly distributed in the matrix material, thereby improving the performance of the material. Softeners can improve the flexibility and processability of the material, making it easier to use. Cross-linking agents can enhance the cross-linking density of the material, improve its strength and durability. Antioxidants can prevent oxidative degradation of the material and extend its service life. Preferred antioxidants include vitamin E, butylated hydroxyanisole, sodium bisulfite and glutathione. Citric acid can be used as a pH regulator and as an antioxidant to help improve the stability and durability of the material. Dispersants include polyvinyl pyrrolidone, polyethylene glycol and ammonium polyacrylate, all of which have good dispersibility and can be selected according to specific application requirements. Softeners include glycerol or triglyceride, all of which have good softening properties and can be selected according to specific application requirements. Crosslinking agents include a mixture of borax and silane coupling agent or a mixture of epoxy resin and silane coupling agent, all of which have good crosslinking properties and can be selected according to specific application requirements.
[0030] In summary, this application uses renewable natural materials as the main ingredients, which is in line with the concept of environmental protection. The reinforcing effect of nanomaterials significantly improves the mechanical properties and waterproof properties of the material. Additives such as antioxidants and citric acid give the material antibacterial and UV protection functions. By selecting different dispersants, softeners and cross-linking agents, materials with different properties can be prepared to meet different application requirements.
[0031] On the other hand, the present invention also proposes a method for preparing an environmentally friendly bio-based nano-enhanced waterproof material, comprising the following steps:
[0032] S1: dissolving chitosan in 1% volume fraction acetic acid solution, stirring to form a chitosan solution, dissolving gelatin and sodium carboxymethyl cellulose in deionized water, stirring until completely dissolved, to form a gelatin solution and a carboxymethyl cellulose solution;
[0033] S2: mixing nano silicon dioxide, nano zinc oxide and nano montmorillonite in a ratio of 7-10:7-10:5-7, adding deionized water, and dispersing the nano silicon dioxide, nano zinc oxide and nano montmorillonite by ultrasonic treatment;
[0034] S3: Mix the chitosan solution, gelatin solution and sodium carboxymethyl cellulose solution in a ratio of 2:2:3 and stir thoroughly; add the dispersed nanoparticles into the mixed solution and continue stirring until uniform;
[0035] S4: adding a cross-linking agent, controlling the reaction temperature and stirring until cross-linking is completed;
[0036] S5: evenly coating the cross-linked solution on a glass plate or a fabric substrate; drying the coated substrate to form a uniform waterproof film; peeling the dried waterproof film from the substrate to form an environmentally friendly bio-based nano-enhanced waterproof material.
[0037] In this preferred embodiment, the ultrasonic treatment time is more than thirty minutes.
[0038] In this preferred embodiment, the cross-linking temperature in S4 is 60° C. and the stirring time is more than two hours.
[0039] It is understandable that the choice of chitosan, gelatin and sodium carboxymethylcellulose: chitosan is a natural polymer derived from chitin, which has good biocompatibility, degradability and antibacterial properties. Gelatin is a protein of animal origin, which has good film-forming properties and biocompatibility. Sodium carboxymethylcellulose is a water-soluble cellulose derivative that provides good adhesion and stability. These materials can produce a synergistic effect by mixing, enhancing the performance of the overall material, such as mechanical strength and water resistance.
[0040] Addition of nanoparticles: nano-silica, nano-zinc oxide and nano-montmorillonite: These nanoparticles have high specific surface area and unique physical and chemical properties, which can significantly enhance the mechanical properties, thermal stability and barrier properties of composite materials.
[0041] Ultrasonic treatment: Through ultrasonic treatment, nanoparticles can be more evenly dispersed in the solution, avoiding agglomeration and ensuring that they can fully play their role in the composite material.
[0042] The cross-linking reaction connects the molecular chains together through chemical bonds to form a three-dimensional network structure, which significantly improves the mechanical strength and water resistance of the material. Control the reaction temperature and time: Stir at 60°C for more than two hours to ensure that the cross-linking reaction is sufficient and improve the overall performance of the material. Uniform coating ensures that the material forms a uniform film layer on the substrate, making the waterproof performance consistent. Drying to form a waterproof film: After drying, a stable waterproof film is formed with good mechanical strength and waterproof performance.
[0043] By using bio-based materials (such as chitosan, gelatin and sodium carboxymethyl cellulose), the pollution to the environment is reduced, which meets the requirements of green environmental protection. Moreover, the addition of nanoparticles significantly improves the mechanical properties, heat resistance and water resistance of the material, making the material perform well in various applications. Most of the bio-based materials used are degradable, avoiding the environmental problems caused by traditional petroleum-based polymers. Natural polymers such as chitosan and gelatin have good biocompatibility, which makes the material also have potential applications in the medical field (such as wound dressings, drug release carriers). Compared with some high-performance synthetic materials, bio-based materials have lower costs, wider sources, and more economic benefits.
[0044] The performance of the material of the present invention is described below by way of examples;
[0045] Embodiment 1:
[0046] S1: dissolving chitosan in 1% volume fraction acetic acid solution, stirring to form a chitosan solution, dissolving gelatin and sodium carboxymethyl cellulose in deionized water, stirring until completely dissolved, to form a gelatin solution and a carboxymethyl cellulose solution;
[0047] S2: mixing nano silicon dioxide, nano zinc oxide and nano montmorillonite in a ratio of 7:7:5, adding deionized water, and dispersing the nano silicon dioxide, nano zinc oxide and nano montmorillonite by ultrasonic treatment for more than 30 minutes;
[0048] S3: Mix the chitosan solution, gelatin solution and sodium carboxymethyl cellulose solution in a ratio of 2:2:3 and stir thoroughly; add the dispersed nanoparticles into the mixed solution and continue stirring until uniform;
[0049] S4: adding a cross-linking agent, controlling the reaction temperature at 60°C and stirring for two hours to complete the cross-linking;
[0050] S5: evenly coating the cross-linked solution on a glass plate or a fabric substrate; drying the coated substrate to form a uniform waterproof film; peeling the dried waterproof film from the substrate to form an environmentally friendly bio-based nano-enhanced waterproof material.
[0051] Embodiment 2:
[0052] S1: dissolving chitosan in 1% volume fraction acetic acid solution, stirring to form a chitosan solution, dissolving gelatin and sodium carboxymethyl cellulose in deionized water, stirring until completely dissolved, to form a gelatin solution and a carboxymethyl cellulose solution;
[0053] S2: mixing nano silicon dioxide, nano zinc oxide and nano montmorillonite in a ratio of 10:10:7, adding deionized water, and dispersing the nano silicon dioxide, nano zinc oxide and nano montmorillonite by ultrasonic treatment for more than 30 minutes;
[0054] S3: Mix the chitosan solution, gelatin solution and sodium carboxymethyl cellulose solution in a ratio of 2:2:3 and stir thoroughly; add the dispersed nanoparticles into the mixed solution and continue stirring until uniform;
[0055] S4: adding a cross-linking agent, controlling the reaction temperature at 60°C and stirring for two hours to complete the cross-linking;
[0056] S5: evenly coating the cross-linked solution on a glass plate or a fabric substrate; drying the coated substrate to form a uniform waterproof film; peeling the dried waterproof film from the substrate to form an environmentally friendly bio-based nano-enhanced waterproof material.
[0057] Embodiment 3:
[0058] S1: dissolving chitosan in 1% volume fraction acetic acid solution, stirring to form a chitosan solution, dissolving gelatin and sodium carboxymethyl cellulose in deionized water, stirring until completely dissolved, to form a gelatin solution and a carboxymethyl cellulose solution;
[0059] S2: mixing nano silicon dioxide, nano zinc oxide and nano montmorillonite in a ratio of 8:9:5, adding deionized water, and dispersing the nano silicon dioxide, nano zinc oxide and nano montmorillonite by ultrasonic treatment for more than 30 minutes;
[0060] S3: Mix the chitosan solution, gelatin solution and sodium carboxymethyl cellulose solution in a ratio of 2:2:3 and stir thoroughly; add the dispersed nanoparticles into the mixed solution and continue stirring until uniform;
[0061] S4: adding a cross-linking agent, controlling the reaction temperature at 60°C and stirring for two hours to complete the cross-linking;
[0062] S5: evenly coating the cross-linked solution on a glass plate or a fabric substrate; drying the coated substrate to form a uniform waterproof film; peeling the dried waterproof film from the substrate to form an environmentally friendly bio-based nano-enhanced waterproof material.
[0063] Comparative Example 1:
[0064] S1: dissolving chitosan in 1% volume fraction acetic acid solution, stirring to form a chitosan solution, dissolving gelatin and sodium carboxymethyl cellulose in deionized water, stirring until completely dissolved, to form a gelatin solution and a carboxymethyl cellulose solution;
[0065] S2: mixing nano silicon dioxide, nano zinc oxide and nano montmorillonite in a ratio of 1:7:5, adding deionized water, and dispersing the nano silicon dioxide, nano zinc oxide and nano montmorillonite by ultrasonic treatment for more than 30 minutes;
[0066] S3: Mix the chitosan solution, gelatin solution and sodium carboxymethyl cellulose solution in a ratio of 2:2:3 and stir thoroughly; add the dispersed nanoparticles into the mixed solution and continue stirring until uniform;
[0067] S4: adding a cross-linking agent, controlling the reaction temperature at 60°C and stirring for two hours to complete the cross-linking;
[0068] S5: evenly coating the cross-linked solution on a glass plate or a fabric substrate; drying the coated substrate to form a uniform waterproof film; peeling the dried waterproof film from the substrate to form an environmentally friendly bio-based nano-enhanced waterproof material.
[0069] Comparative Example 2:
[0070] S1: dissolving chitosan in 1% volume fraction acetic acid solution, stirring to form a chitosan solution, dissolving gelatin and sodium carboxymethyl cellulose in deionized water, stirring until completely dissolved, to form a gelatin solution and a carboxymethyl cellulose solution;
[0071] S2: mixing nano silicon dioxide, nano zinc oxide and nano montmorillonite in a ratio of 7:1:5, adding deionized water, and dispersing the nano silicon dioxide, nano zinc oxide and nano montmorillonite by ultrasonic treatment for more than 30 minutes;
[0072] S3: Mix the chitosan solution, gelatin solution and sodium carboxymethyl cellulose solution in a ratio of 2:2:3 and stir thoroughly; add the dispersed nanoparticles into the mixed solution and continue stirring until uniform;
[0073] S4: adding a cross-linking agent, controlling the reaction temperature at 60°C and stirring for two hours to complete the cross-linking;
[0074] S5: evenly coating the cross-linked solution on a glass plate or a fabric substrate; drying the coated substrate to form a uniform waterproof film; peeling the dried waterproof film from the substrate to form an environmentally friendly bio-based nano-enhanced waterproof material.
[0075] Comparative Example 3:
[0076] S1: dissolving chitosan in 1% volume fraction acetic acid solution, stirring to form a chitosan solution, dissolving gelatin and sodium carboxymethyl cellulose in deionized water, stirring until completely dissolved, to form a gelatin solution and a carboxymethyl cellulose solution;
[0077] S2: mixing nano silicon dioxide, nano zinc oxide and nano montmorillonite in a ratio of 7:7:1, adding deionized water, and dispersing the nano silicon dioxide, nano zinc oxide and nano montmorillonite by ultrasonic treatment for more than 30 minutes;
[0078] S3: Mix the chitosan solution, gelatin solution and sodium carboxymethyl cellulose solution in a ratio of 2:2:3 and stir thoroughly; add the dispersed nanoparticles into the mixed solution and continue stirring until uniform;
[0079] S4: adding a cross-linking agent, controlling the reaction temperature at 60°C and stirring for two hours to complete the cross-linking;
[0080] S5: evenly coating the cross-linked solution on a glass plate or a fabric substrate; drying the coated substrate to form a uniform waterproof film; peeling the dried waterproof film from the substrate to form an environmentally friendly bio-based nano-enhanced waterproof material.
[0081] Waterproof performance test:
[0082] According to the national standard GB / T 328.1-2014 "Building Waterproofing Membrane Part 1: Asphalt Waterproofing Membrane" or the corresponding industry standards, use a waterproof testing machine for testing. Conduct an immersion test, immerse the material sample in water for a certain period of time, and observe its water absorption rate. Conduct a pressure test, fix the material sample on the testing machine, apply a certain pressure, and observe whether the material leaks.
[0083] Mechanical strength test:
[0084] According to the national standard GB / T 528-2009 "Determination of tensile properties of vulcanized rubber or thermoplastic rubber" or the corresponding industry standards, use a universal testing machine to test the tensile strength and elongation at break. Perform compression strength tests to detect the mechanical properties of materials under compression.
[0085] Durability testing:
[0086] Conduct aging tests, such as UV aging and heat aging, to simulate the long-term performance of materials in actual use environments. Conduct durability tests in accordance with the national standard GB / T 17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels".
[0087] Biocompatibility and antimicrobial testing:
[0088] The biocompatibility test was conducted in accordance with the national standard GB / T 16886.1-2011 "Biological evaluation of medical devices Part 1: Evaluation and testing". The antibacterial performance test was conducted in accordance with the national standard GB / T 20944.1-2007 "Antibacterial plastics Part 1: Determination of antibacterial effect".
[0089] Environmental performance testing:
[0090] Check whether the material contains harmful substances, such as heavy metals, volatile organic compounds (VOCs), etc., and refer to the corresponding national standards such as GB / T 18401-2010 "Technical Specifications for Safety of Textile Products". Conduct environmental degradation performance tests on the material to verify its biodegradability.
[0091]
[0092] It can be seen from the above table that the mechanical strength of Comparative Example 1 is far inferior to that of Examples 1-3, and the antibacterial property of Comparative Example 2 is also inferior to that of Examples 1-3. The water permeability of Comparative Example 3 is too high, indicating that its waterproof performance is inferior to that of Examples 1-3.
[0093] In summary, the present invention provides an environmentally friendly bio-based nano-enhanced waterproof material, in which the bio-based fillers and nano-materials used are environmentally friendly materials, which can reduce dependence on petroleum resources and reduce environmental pollution. By introducing modified nano-silicon dioxide, nano-zinc oxide and nano-montmorillonite, the waterproof performance of the material is significantly improved, making it suitable for a variety of occasions with high waterproof requirements. The cross-linking agent in the present invention can effectively improve the bonding force between the bio-based filler and the nano-material, thereby enhancing the mechanical strength and durability of the material. The added antioxidant and citric acid can improve the antioxidant performance of the material and extend the service life of the material. The combination of the bio-based filler and the nano-material in the present invention not only provides excellent waterproof performance, but also gives the material good biocompatibility and antibacterial properties. The preparation method of the present invention is simple, easy to operate, suitable for large-scale production, and conducive to reducing production costs. The environmentally friendly bio-based nano-enhanced waterproof material of the present invention can be widely used in the fields of construction, transportation, aerospace, etc., and has broad market prospects.
[0094] On the other hand, the present invention also proposes an environmentally friendly bio-based nano-enhanced waterproof material for use in the fields of construction, transportation, and aerospace.
[0095] Since the material has excellent waterproof performance, mechanical strength and durability, as well as environmental protection and biocompatibility, it can be used in the fields of construction, transportation, and aerospace.
[0096] Construction: As a roof waterproofing layer, this material can effectively prevent rainwater penetration, extend the service life of the roof, and reduce maintenance costs. In areas susceptible to moisture, such as basements and bathrooms, this material can provide long-lasting waterproof protection to prevent the growth of mold and bacteria.
[0097] Transportation: In roads, bridges, tunnels and other projects, this material can be used as a waterproof and anti-seepage treatment layer to ensure the stability and durability of roads and structures under adverse weather conditions. In the maintenance and repair of transportation infrastructure, this material can provide a fast and effective waterproofing solution, reducing construction time and costs.
[0098] Aerospace: As a waterproof and moisture-proof material for the internal structure of aircraft, this material can protect electronic equipment and passengers from moisture, improving flight safety and comfort. In the manufacturing process of aircraft, this material can be used for sealing and waterproofing to ensure the performance stability of the aircraft under different climatic conditions.
[0099] Moreover, natural polymers such as chitosan and gelatin have good biocompatibility, which makes this material also potentially applicable in the medical field (such as wound dressings and drug release carriers).
[0100] Wound dressing: As a wound dressing, the material can provide a good moist environment, promote wound healing, and prevent bacterial infection. Due to its biocompatibility, the material will not cause inflammatory reactions around the wound, which is conducive to the rapid healing of the wound.
[0101] Drug release carrier: As a drug release carrier, this material can accurately control the release rate and time of the drug, achieving precise control of the drug. Due to its good biocompatibility, this material can be safely used inside the human body, such as an implantable drug release system.
[0102] In summary, the present invention provides an environmentally friendly bio-based nano-enhanced waterproof material, in which the bio-based fillers and nano-materials used are environmentally friendly materials, which can reduce dependence on petroleum resources and reduce environmental pollution. By introducing modified nano-silicon dioxide, nano-zinc oxide and nano-montmorillonite, the waterproof performance of the material is significantly improved, making it suitable for a variety of occasions with high waterproof requirements. The cross-linking agent in the present invention can effectively improve the bonding force between the bio-based filler and the nano-material, thereby enhancing the mechanical strength and durability of the material. The added antioxidant and citric acid can improve the antioxidant performance of the material and extend the service life of the material. The combination of the bio-based filler and the nano-material in the present invention not only provides excellent waterproof performance, but also gives the material good biocompatibility and antibacterial properties. The preparation method of the present invention is simple, easy to operate, suitable for large-scale production, and conducive to reducing production costs. The environmentally friendly bio-based nano-enhanced waterproof material of the present invention can be widely used in the fields of construction, transportation, aerospace, etc., and has broad market prospects; by adopting bio-based materials (such as chitosan, gelatin and sodium carboxymethyl cellulose), the pollution to the environment is reduced, which meets the requirements of green environmental protection. Moreover, the addition of nanoparticles significantly improves the mechanical properties, heat resistance and water resistance of the material, making the material perform well in various applications. Most of the bio-based materials used are degradable, avoiding the environmental problems caused by traditional petroleum-based polymers. Natural polymers such as chitosan and gelatin have good biocompatibility, which makes the material also potentially applicable in the medical field (such as wound dressings and drug release carriers). Compared with some high-performance synthetic materials, bio-based materials have lower costs, wider sources, and are more economical.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. An environmentally friendly bio-based nano-enhanced waterproof material, characterized in that: The proportion of each raw material is as follows: 80-100 parts of bio-based filler, 7-10 parts of modified nano silicon dioxide, 7-10 parts of nano zinc oxide, 5-7 parts of nano montmorillonite, 3-5 parts of dispersant, 3-5 parts of softener and 2-3 parts of cross-linking agent.
2. The environmentally friendly bio-based nano-enhanced waterproof material according to claim 1, characterized in that: It also includes 1-2 parts of antioxidant and 1-2 parts of citric acid; wherein the antioxidant is one or a mixture of vitamin E, butylated hydroxyanisole, sodium bisulfite and glutathione.
3. The environmentally friendly bio-based nano-enhanced waterproof material according to claim 2, characterized in that: The bio-based filler is one or a mixture of chitosan, gelatin and sodium carboxymethyl cellulose.
4. The environmentally friendly bio-based nano-enhanced waterproof material according to claim 3, characterized in that: The dispersant is one or a mixture of polyvinyl pyrrolidone, polyethylene glycol and ammonium polyacrylate.
5. The environmentally friendly bio-based nano-enhanced waterproof material according to claim 4, characterized in that: The softener is glycerol or triglyceride.
6. The environmentally friendly bio-based nano-enhanced waterproof material according to claim 5, characterized in that: The crosslinking agent is one of a mixture of borax and silane coupling agent in a ratio of 3 parts borax to 1 part silane coupling agent or a mixture of epoxy resin and silane coupling agent in a ratio of 10 parts epoxy resin to 1 part silane coupling agent.
7. A method for preparing an environmentally friendly bio-based nano-enhanced waterproof material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: dissolving chitosan in 1% volume fraction acetic acid solution, stirring to form a chitosan solution, dissolving gelatin and sodium carboxymethyl cellulose in deionized water, stirring until completely dissolved, to form a gelatin solution and a carboxymethyl cellulose solution; S2: mixing nano silicon dioxide, nano zinc oxide and nano montmorillonite in a ratio of 7-10:7-10:5-7, adding deionized water, and dispersing the nano silicon dioxide, nano zinc oxide and nano montmorillonite by ultrasonic treatment; S3: Mix the chitosan solution, gelatin solution and sodium carboxymethyl cellulose solution in a ratio of 2:2:3 and stir thoroughly; add the dispersed nanoparticles into the mixed solution and continue stirring until uniform; S4: adding a cross-linking agent, controlling the reaction temperature and stirring until cross-linking is completed; S5: evenly coating the cross-linked solution on a glass plate or a fabric substrate; drying the coated substrate to form a uniform waterproof film; peeling the dried waterproof film from the substrate to form an environmentally friendly bio-based nano-enhanced waterproof material.
8. The method for preparing an environmentally friendly bio-based nano-enhanced waterproof material according to claim 7, characterized in that: The ultrasonic treatment time is at least thirty minutes.
9. The method for preparing an environmentally friendly bio-based nano-enhanced waterproof material according to claim 8, characterized in that: In the S4, the cross-linking temperature is 60° C. and the stirring time is at least two hours.
10. Application of the environmentally friendly bio-based nano-enhanced waterproof material according to any one of claims 1 to 6 in the fields of construction, transportation, and aerospace.
Citation Information
Cited By
Environment-friendly biodegradable waterproof coiled material and preparation method thereof
CN119610800A
Environment-friendly biodegradable waterproofing membrane and preparation method thereof
CN119610800B
